2020
DOI: 10.1002/ieam.4253
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Metals in Soil and Tissues of Economic‐Interest Plants Grown in Sites Affected by the Fundão Dam Failure in Mariana, Brazil

Abstract: The objective of this study was to evaluate the concentration of potentially toxic elements in Brachiaria decumbens, Stylosanthes guianensis, and Saccharum officinarum plants and soil samples in affected and unaffected areas by rupture of the Fundão dam, Brazil. Samples were collected in areas affected by residues from the Fundão dam (RAA1, RAA2, RAA3) and in an unaffected area (control). The material was analyzed for the composition of micronutrients and trace elements in soil and plants, as well as contamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 46 publications
(60 reference statements)
4
14
1
2
Order By: Relevance
“…The mining waste mud increased the levels of Fe, Al, Mn, Cu, and Cr in the soil and in the tissues of plants from the affected areas (Coelho et al., 2020; Segura et al., 2016; Silva et al., 2016). These elements induce cytotoxic, genotoxic, and mutagenic effects in plants, reducing germination and mitotic indexes (Segura et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mining waste mud increased the levels of Fe, Al, Mn, Cu, and Cr in the soil and in the tissues of plants from the affected areas (Coelho et al., 2020; Segura et al., 2016; Silva et al., 2016). These elements induce cytotoxic, genotoxic, and mutagenic effects in plants, reducing germination and mitotic indexes (Segura et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These elements induce cytotoxic, genotoxic, and mutagenic effects in plants, reducing germination and mitotic indexes (Segura et al., 2016). Also, the level of As in contaminated soil samples was above the prevention value (CONAMA, 2009), but this element has natural anomalous background levels in the soil of the Iron Quadrangle region (Guerra et al., 2017) and has not been verified in plants (Coelho et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…No significant differences was found between affected and nonaffected areas soil Cu contents in this study. However, Coelho et al (2020) found higher concentrations of Cu in both affected areas (17 mg/kg) and control areas (7.3 mg/kg) and also pointed out that the tailing deposition reduced the soil Cu contents. Copper concentrations in soil samples may be related to the natural presence of amphibole and biotite gneiss in the region (CPRM, 2004).…”
Section: Discussionmentioning
confidence: 96%
“…Thus, considering that in the study region, B. decumbens is the main cattle feed fodder, a Cu supplementation for these cattle may even be recommended. Coelho et al (2020) also analyzed B. decumbens cultivated in the affected region by the iron tailings and found similar copper content that ranged from 21.1 to 48.3 mg/kg. Unlike the present study, these authors found higher levels of copper in the affected areas compared with control ones.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation